Self-defense in Islamic and international law assessing Al-Qaeda and the invasion of Iraq - Shah, Niaz A. (Palgrave MacMillan, 2008)
The book argues that the concept of self-defense in Islamic and International law is compatible. Al-Qaeda's declaration of Jihad does not meet the Islamic legal test. Similarly, the invasion of Iraq does meet the international legal test.